Collaural Fistula on the Left-side of the Face: A Case Report - SAGAR GAURKAR; CHANDRAVEER SINGH; JASLEEN KAUR; PRASAD T DESHMUKH (Journal of Clinical and Diagnostic Research, 2024)
Collaural fistula, also known as cervico-aural fistula, is a rare anomaly that accounts for less than 8% of all branchial cleft anomalies. These fistulas result from incomplete closure of the first branchial cleft during embryonic development. A 21-year-old female exhibited depression on the left-side of her face since childhood, accompanied by a fistula. She had a history of intermittent discharge and a tuft of hair emerging from it. Additionally, the patient reported left ear discharge and an opening in the floor of the External Auditory Canal (EAC). Diagnostic imaging, including X-ray fistulogram, ultrasound, and Magnetic Resonance Imaging (MRI) neck fistulogram, played a crucial role in confirming the diagnosis of a collaural fistula. Surgical intervention involved excision of the fistulous tract and reconstruction of the EAC floor. The patient received antibiotic therapy, resulting in successful postoperative outcomes. The present case highlights the importance of recognising and appropriately managing collaural fistulas. When these fistulas are discovered early, along with a solid grasp of regional embryology and anatomy, there is a chance for better treatment outcomes.